Effect of fermented pumpkin (Cucúrbita pepo) on the productive and health parameters in pre-fattening pigs - Medina-González, Rafael; Ortiz-Milán, Abel; Elias-Iglesias, Arabel; Álvarez-Villar, Victor M.; Brea-Maure, Odelin (Universidad Pedagógica y Tecnológica de Colombia, 2019)
There were used 30 pre-fattening pigs of Yorkshire x Landrace hybrid, 7 kg average weight, during 42 days, coinciding between 33 to 76 days of the pigs´ age, with the objective of replacing the 0 (control); 15 and 30% of the conventional feed for the fermented pumpkin, according to completely randomized design with three treatments and ten repetitions, each baby was considered as a repetition. The concentration of yeasts in the pumpkin fermentation was determined, where an apparent stability in the concentration of these microorganisms was observed 21 days after the fermented was elaborated, while in the pigs the final live weight (27.30, 28.00 and 27.50 kg), the average daily gain (483, 502 and 488 g / day), the consumption of dry matter (30.37, 30.38 and 30.33 kg) and the conversion of dry matter (1.50, 1.44 and 1.48 kg DM / kg PV respectively) did not present a significant difference between the treatments evaluated; however, in the control treatment, there were more animals with diarrhea and mortality reached 10%; while in treatments that included fermented pumpkin, the rate of diarrhea was minimal and deaths were nil. It is concluded that pumpkin fermentation did not affect the productive indicators of pre-fattening pigs, while reducing the occurrence of diarrhea and avoiding deaths in this technological category.